Effective Reading Techniques for English for Young Learners - Rosalina, Irene; Salam, Hamidah (Journal of Linguistics and Social Studies, 2024)
Reading is an important skill to be mastered by the learners. How and when a child learns to read is one of the key educational milestones. Positive communication between the teacher and the student facilitates the easy acquisition of reading comprehension abilities (Ramsa Rawian, 2021). Reading calls for specialized training as well as deliberate effort (Ericsson, 2008). It is not a simple undertaking to teach English to young learners. In order to keep students interested and motivated in the teaching and learning process, teachers must employ effective teaching strategies (Ayua, 2017). Therefore, a study on the theme of how effective reading strategies for young learners are employed in this research is conducted. Library research was done as a method to enrich the insight and answer the question. Some reading strategies are advised to be applied in teaching reading, such as emergent literacy, the Mnemonic Technique, Read-Aloud techniques, Deciphering techniques, and the Language Experience Method.